'Writing the lives of painters' : biography and artistic identity in Britain 1760-1810 - Junod, Karen, 1973- (Oxford : Oxford University Press, 2011)
This book explores the development of artists' biographies in the cultural context of 18th- and early 19th-century Britain. It argues that the proliferation of a myriad biographical forms mirrored the privileging of artistic originality and difference within an art world that had yet to generate a coherent 'British School' of painting.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Keywords: Biography as a literary form; Art and literature -- Great Britain -- History -- 18th century; Art and literature -- Great Britain -- History -- 19th century